The Impact of E-Learning on Enhancing EFL Teachers' Performance in the Teaching- Learning Process (A Case Study of University of Gezira Students) - Min Alseed Mohamed, Mawaddah Ibrahim (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 1 (2023), 2026)
The study aims at investigating the possibilities of using e-learning programs in EFL learners’ higher institutions and  motivating them to learn through modern methods. In addition, the study aims to enhance the EFL teaching- learning process. The researcher used a questionnaire for data collection. It was distributed to twenty (20) EFL learners  for data collection at the Faculty of Education - Elhasahisa, University of Gezira, Sudan. Then the collected data was statistically analyzed through the (SPSS) program. The results indicate that, using e-learning requires users to gain special skills of interacting through technology as this allows teachers to have more learner-centered classroom environment. Moreover, e-learning motivates the learners to learn through authentic learning sources. Furthermore, EFL learners’ collaboration through multimedia is enjoyable and permits data saving, sharing and updating. E-learning develops EFL learners’ critical thinking skills and also enables distant learners to interact. Practicing e-learning improves EFL learners’ language skills and enables them to perform cross cultural communication. However,  the use of e-learning programs, in  Sudanese Universities still needs more efforts from instructors as well as students. The study recommends that e-learning should be applied in EFL classes and learners should be trained on using e-learning. تهدف الدراسة إلى إمكانية تقصي دور التعليم الالكتروني في عملية التدريس والتعلّم  لطلاب اللغة الإنجليزية كلغة أجنبية في مؤسسات التعليم العالي و تحفيزهم من خلال  التعليم الإلكتروني وتسهيل عملية التدريس والتعليم من خلال استخدام برامج الكمبيوتر التعليمية الحديثة. استخدمت الباحثة المنهج التحليلي الوصفي كما استخدمت الدراسة الاستبانة كأداة لجمع البيانات من عينة مكونة من عشرين (20) طالباً وطالبة بكلية التربية الحصاحيصا جامعة الجزيرة -السودان. بعد جمع البيانات وتحليلها إحصائياً باستخدام برنامج الحزم الإحصائية للعلوم الاجتماعية (SPSS) توصلت الدراسة للآتي: استخدام التقنيات الحديثة في التدريس والتعلّم يتطلب معرفة المدرسين والطلاب  لأساليب للتواصل عبر الأجهزة الحديثة، إذ إن التعليم الإلكتروني يفتح آفاقاً جديدة للمعلمين والطلاب لجعل التعلّم مركزاً على الطلاب في التواصل, يتمكن الطلاب من الحصول على المواد التعليمية من مصادر أصلية .كما يتمكن الطلاب من حفظ وإعادة استعمال المواد الدراسية. إن الدروس المبرمجة في الأجهزة الالكترونية ممتعة ومحفزة للطلاب للعمل الجماعي والتواصل الثقافي، كما أن الدروس المبرمجة تطّور مهارات التفكير النقدي لدي الطلاب، كما أنّها تمكن  الدارسين عن بعد  من التفاعل العلمي، و قد توصلت الدراسة أيضاً إلى أن التعليم الإلكتروني في الجامعات السودانية يحتاج لمجهودات أكثر للتدريب على  التدريس والتعلّم عبر التقنيات الحديثة. أوصت الدراسة باستخدام التعليم الإلكتروني في صفوف تدريس اللغة الإنجليزية وتدريب الدارسين على استخدامه.